2004
DOI: 10.1521/suli.34.2.177.32781
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Harmful Behaviors in a Population‐Based Sample of Young Adults

Abstract: A birth cohort of 472 women and 494 men aged 26 years was interviewed about a range of self-harmful behaviors first and then asked about suicidal intent. Lifetime prevalence of self-harm using traditional methods of suicide (ICD [International Classification of Diseases] self-harm) was 13%, with 9% of the sample describing at least one such episode as "attempted suicide." Other self-harmful behaviors were common; 14% of women and 33% of men reported self-battery. ICD self-harm over the past year was reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 15 publications
2
55
0
3
Order By: Relevance
“…They were assessed at age 3, and thereafter biennially until 15, and at ages 18, 21, 26, 32, and 38 years (Poulton et al, 2015). At age 26 (1998–1999), 472 women and 494 men, consented to an interview on self-harm behaviors (Nada-Raja et al, 2004). The sample represents all socioeconomic levels (Poulton et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were assessed at age 3, and thereafter biennially until 15, and at ages 18, 21, 26, 32, and 38 years (Poulton et al, 2015). At age 26 (1998–1999), 472 women and 494 men, consented to an interview on self-harm behaviors (Nada-Raja et al, 2004). The sample represents all socioeconomic levels (Poulton et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…At age 26, participants completed a 20 minute semi-structured in-person interview on self-harm thoughts and behaviors (Nada-Raja et al, 2004). Self-harm questions were asked about behaviors with the intent of hurting onself in the context of dealing with mental or psychological pain, emotions, or stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More focused epidemiological studies suggest a 12-month prevalence estimate of 7.3 % among US adolescents (Taliaferro et al, 2013). The prevalence estimates of NSSI in young adults (aged 18-25 years) have centered around 17 %, with individual studies reporting rates ranging between 5 and 35 % (Gratz, 2001;Nada-Raja, Skegg, Langley, Morrison & Sowerby, 2004;Whitlock et al, 2011). In the US current rates of NSSI among adults (typically including ages 25 and older) are estimated to be around 5 % (Klonsky, 2011).…”
Section: Prevalence Of Nssi and Edmentioning
confidence: 99%
“…Some studies in the literature reported a correlation between NSSI and socioeconomic level, being abused, problems about friendship relations, psychological disorders like depression, anxiety, behavior disorders and suicide ideation along with several risky disorders like smoking, alcohol consumption, school skipping 4,[12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%